Preclinical Efficacy and Proteomic Prediction of Molecular Targets for s-cal14.1b and s-cal14.2b Conotoxins with Antitumor Capacity in Xenografts of Malignant Pleural Mesothelioma - Angélica Luna-Nophal; Fernando Díaz-Castillo; Vanessa Izquierdo-Sánchez; Jesús B. Velázquez-Fernández; Mario Orozco-Morales; Luis Lara-Mejía; Johana Bernáldez-Sarabia; Noemí Sánchez-Campos; Oscar Arrieta; José Díaz-Chávez; Jorge-Ismael Castañeda-Sánchez; Alexei-Fedorovish Licea-Navarro; et al. (Marine Drugs)
Malignant pleural mesothelioma (MPM) is a rare neoplasm with increasing incidence and mortality rates. Although recent advances have improved the overall prognosis, they have not had an important impact on survival of patients with MPM, such that more effective treatments are needed. Some species of marine snails have been demonstrated to be potential sources of novel anticancer molecules. This study analyzed the anticancer effects in vitro and in vivo of two peptides found in C. californicus. The effects of s-cal14.1b and s-cal14.2b on cell proliferation, apoptosis, and cytotoxicity were evaluated in 2D and 3D cultures of MPM-derived cells. Proteomics analysis of 3D cultures treated with conotoxins was performed to examine changes in expression or abundance. And the therapeutic effects of both conotoxins were evaluated in MPM mouse xenografts. s-cal14.1b and s-cal14.2b induced apoptosis and cytotoxicity in 2D and 3D cultures. However, only s-cal14.1b modified spheroid growth. Approximately 600 proteins exhibited important differential expression, which was more heterogeneous in H2452 vs MSTO-211H spheroids. The in silico protein functional analysis showed modifications in the biological pathways associated with carcinogenesis. CAPN1, LIMA1, ANXA6, HUWE1, PARP1 or PARP4 proteins could be potential cell targets for conotoxins and serve as biomarkers in MPM. Finally, we found that both conotoxins reduced the tumor mass in MPM xenografts; s-cal14.1b reached statistical significance. Based on these results, s-cal14.1b and s-cal14.2b conotoxins could be potential therapeutic drugs for MPM neoplasms with no apparent side effects on normal cells.